Identification of a Novel KTi-1 Allele Associated with Reduced Trypsin Inhibitor Activity in Soybean Accessions - Aron Park; Se-Hee Kang; Byeong-Hee Kang; Sreeparna Chowdhury; Seo-Young Shin; Won-Ho Lee; Jeong-Dong Lee; Sungwoo Lee; Yu-Mi Choi; Bo-Keun Ha (Agriculture, 2023)
Trypsin inhibitors (TIs) in soybean seeds reduce the availability of processed soybean foods and animal feed. This study aimed to evaluate the trypsin inhibitor activity (TIA) in 999 Korean soybean accessions and conduct molecular characterization of soybean accessions with low TIA. TIA was evaluated using colorimetric analysis through a substrate–enzyme reaction. The average TIA of the 999 soybean accessions was 90.31%, ranging from 43.70% to 99.51%. Kunitz trypsin inhibitor 3 (KTi-3) gene target sequencing analysis was performed on seven soybean germplasm accessions (IT105782, IT170889, IT273590, IT274513, IT274515, IT276197, and IT022891) showing less than 60% TIA. Four soybean accessions (IT274513, IT274515, IT276197, and IT022891) exhibited the same mutations (a G-to-T transversion and an AG deletion) in the KTi-3 gene (Glyma.08g341500) in PI542044. In addition, whole-genome re-sequencing was performed on three soybean accessions with no mutations in the KTi-3 gene. Compared with the reference soybean genome, an in-frame insertion and five missense mutations were identified in the coding sequencing of the KTi-1 gene (Glyma.01g09500) in IT105782. A RT-qPCR analysis showed that the mRNA expression level of KTi-1 was reduced by approximately 17% in IT105782 during seed development. In this study, we identified a previously unreported mutation in the KTi-1 gene and developed a KASP marker using this new KTi-1 variant.